Problematika Transliterasi Al-Qur’an - Abdul Rosyid (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2021)
This article will discuss the problems of transliteration of the Qur’an based on the SKB2M Republic of Indonesia which does not provide detailed guidance on the transfer of the Qur’anic letter into Latin script (Indonesia). So that it can make readers who are illiterate the Qur’an unable to recognize the Qur’anic letter because of the different spelling directions. For this reason, this article will present an alternative transcription guide specifically designed to transcribe the Qur'an so as to help the illiterate of the Qur'an to have the spirit of learning to read the Qur'an.